Hubungan Antara Motivasi Belajar dan Kecemasan pada Siswa Kelas Vi Sekolah Dasar di Denpasar Menjelang Ujian Nasional - Suardana, Anak Agung Putu Chintya Putri; Simarmata, Nicholas (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
Problems arise where elementary school student’s anxiety increased with the grade level when faced with the evaluation or examination. The problems were most often experienced by students when they will face the exam is a matter of anxiety. Lack of preparation when facing national exam can be overcome by increasing students studying motivation .This study aimed to determine the relationship between studying motivation and anxiety at sixth grade student’s elementary schools in Denpasar ahead national exam . This research is a quantitative correlation research. The subjects were 100 sixth grade elementary school students in Denpasar. Method of sample collection is by cluster random sampling method. Methods of data collection are Studying Motivation Scale which its reliability is 0.804 and Anxiety Scale which its reliability is 0.908. Normality of studying motivation variable is 0.148 and anxiety variable is 0.671. Linearity of variable studying motivation and anxiety variable is 0.002. Data analysis method is Pearson product moment correlation technique. The results show that there is a significant negative relationship between studying motivation and anxiety at Sixth Grade Students Elementary School in Denpasar Ahead of National Exam which its coefficient correlation is -0.303 with its probability value is 0.001. Key words: Studying Motivation, Anxiety, National Exam, Sixth Grade Students, Elementary SchoolProgram Studi Psikologi, Fakultas Kedokteran, Universitas Udayana